2012
DOI: 10.1021/cs300179q
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Nano-Silica Supported Ruthenium (KCC-1/Ru): A Sustainable Catalyst for the Hydrogenolysis of Alkanes with Good Catalytic Activity and Lifetime

Abstract: We have shown that fibrous nanosilica (KCC-1) can serve as a suitable support for the synthesis of highly dispersed ruthenium (Ru) nanoparticles. The resulting KCC-1/Ru catalyst displayed superior activity for the hydrogenolysis of propane and ethane at atmospheric pressure and at low temperature. The high catalytic activity was due to the formation of Ru-nanoparticles with an active size range (1−4 nm) and the presence of hexagonal-shaped particles with several corners and sharp edges possessing reactive atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(110 citation statements)
references
References 44 publications
1
107
0
1
Order By: Relevance
“…In recent study, Fihri et al reported the application of fibrous nano-silica supported ruthenium (KCC-1/Ru) in hydrogenolysis of alkanes[55]. The results showed that high catalytic activity was due to the highly accessible KCC-1 support while excellent stability was probably due to the fibrous nature of the support.…”
mentioning
confidence: 99%
“…In recent study, Fihri et al reported the application of fibrous nano-silica supported ruthenium (KCC-1/Ru) in hydrogenolysis of alkanes[55]. The results showed that high catalytic activity was due to the highly accessible KCC-1 support while excellent stability was probably due to the fibrous nature of the support.…”
mentioning
confidence: 99%
“…It should be noted, that hydrogenolysis is a common trend for Ru-based catalysts [6]. Thus, hydrogenolysis of alkylphenols and phenolic ethers was earlier reported in [57], while hydrolysis of alkanes was observed in [105].…”
Section: Hydrogenation Of Phenols In the Presence Of Heterogeneous Dementioning
confidence: 99%
“…With the advent of nanoscience, chemists achieved that the best solution to lower activity limitation of heterogeneous catalysts is to keep the size of the particles in the heterogeneous catalyst as small as possible. Nowadays a wide variety of nanostructured catalysts or catalytic systems immobilized on nanostructured supports have been applied in various catalytic reactions and as results heterogeneous catalytic systems recently have attracted much attention [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%